Perbedaan Kinerja Keuangan dan Leverage Antara Perusahaan yang Mengalami Financial Distress dengan Perusahaan yang Tidak Mengalami Financial Distress - Melati, Rima; Suranta, Eddy (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to provide empirical evidence of significant differences in ESG scores, return on asset ratios, return on equity ratios, leverage, and BIG4 from companies experiencing financial distress and those not experiencing financial distress. This research uses two theories, namely impression management theory and legitimacy theory, where companies with ESG scores are considered better than others. The companies used in this research are all companies that have ESG scores, and the sample companies selected are manufacturing companies that have ESG scores. The number of samples used was 24 companies, with a research period from 2018-2022. All hypotheses were tested using two independent sample t-tests. The test results prove a significant difference in ESG score, ROA ratio, ROE ratio, leverage, and BIG4 between financially distressed and non-financially distressed companies. This research provides additional empirical evidence in explaining impression management and legitimacy theories.